Otimização da alocação de PMUs em redes elétricas com infraestrutura de comunicações - Cruz, Marco António do Rosário Santos (2016)
This work presents a new optimization algorithm for minimum total costs in WAMS (Wide Area Monitoring Systems) based on Phasor Measurement Units (PMUs). This method seeks to combine the optimal allocation of PMUs with communication infrastructure design, restricted to the lowest total cost of measurement system. State Estimation (EE) is a must-stage monitoring of power systems and ensures system security and appropriate power flows. Until recently, Remote Terminal Units (RTUs) were the main responsible for collecting measurements of active and reactive power flows, active and reactive power injection and voltage module in buses to SCADA (Supervisory Control And Data Acquisition) System, which in turn supplies data to EE. The introduction of PMUs in 1990 brought comparative advantage since the measurements are synchronized by use of Global Positioning System (GPS), which allows efficient WAMS be in control and operation. Another advantage is the PMUs high data sampling combined with EE, which ensures quick control voltage compared to conventional measurements. However, using PMUs technology entails a considerable cost and therefore early has set up the Optimal PMU Placement (OPP) problem on transmission network, without compromising EE. Many OPP algorithms have been proposed taking into account criteria such as observability, single contingencies such as single PMU outage cases, single branch failure and measures and critical assemblies. But most focuses on simple minimization of PMUs and its placement. A few recent studies have called attention to other costs such as the Communication Infrastructure, which have greater contribution on monitoring system costs than PMUs. Thus, the problem would be formulated in a more comprehensive manner, seeking to optimize the total costs, which would mean optimize the allocation of PMUs and communications infrastructure. This paper proposes to give more contribution in this approach and presents a new cost optimal method on WAMS, considering the meters and communication costs. It is based on graph theory to model the problem as a problem of determining a Minimum Connected Dominating Set (theory of graphs). Thus, a methodology is implemented through a metaheuristic - VNS (Variable Neigbourhood Search)- combined with two algorithms, Dijkstra (shortest paths) and Kruskal (minimum spanning tree). This paper explores various metrics of graph theory and proposes new ones to boost algorithm performance; and is incorporated to the model aspects and restrictions closer to practical reality of WAMS. Also it adds up a scalable algorithm feature, applicable from small systems to large and complex.